Capital market reaction to the United States-China trade war: an event study of abnormal return, trading volume activity, and market capitalization in Indonesian coal sub-sector companies - Gio Andri Alkana Ginting; Lawren Julio Rumokoy; Emilia Margareth Gunawan (Yayasan Widyantara Nawasena Raharja, 2026)
This study examines the capital market reaction to the United States-China trade war among coal sub-sector issuers listed on the Indonesia Stock Exchange (IDX), using an event study approach with Abnormal Return (AR), Trading Volume Activity (TVA), and Market Capitalization (MC) as reaction indicators. The final sample consists of 14 coal sub-sector companies selected through purposive sampling based on continuous listing, absence of confounding corporate actions, and complete price/volume data throughout the observation period. The event window spans 29 trading days (t−14 to t+14) surrounding the tariff escalation of April 16, 2025 (t=0), preceded by a 15-trading-day estimation window (t−29 to t−15) used to construct the expected return under the Mean-Adjusted Model. Because the AR, TVA, and MC data did not fully satisfy the normality assumption under the Shapiro-Wilk test, the non-parametric Wilcoxon Signed Rank Test was used for hypothesis testing. The results show no statistically significant difference in AR before and after the event (Z = -0.408, p = 0.683), whereas TVA (Z = -2.480, p = 0.013) and MC (Z = -3.296, p = 0.001) both differ significantly. These findings indicate that the trade war was not strong enough to alter abnormal profits captured through returns, but significantly affected trading activity and the market's valuation of coal issuers, suggesting that the reaction was channeled primarily through liquidity and valuation responses rather than price adjustments. Theoretically, this study extends the Efficient Market Hypothesis and geopolitical risk theory by showing that market efficiency can manifest asymmetrically across reaction channels; practically, it offers investors, portfolio managers, and issuers in China-exposed commodity sectors an evidence-based basis for monitoring liquidity and valuation signals, rather than price movements alone, during periods of trade-policy escalation.